Landscape archaeology in the near east : approaches, methods and case studies - Arikan, Bülent,; Olsvig-Whittaker, Linda, (Archaeopress Archaeology, 2023)
Collected papers from the 3rd symposium of the the Society for Near Eastern Landscape Archaeology. Ranging from the Palaeolithic to the classical Near East, papers consider settlement and movement for trade with an overarching theme around the conservation of important archaeological landscapes and developing technology for the study of landscapes.